Unveiling the Mechanisms for Decreased Glutathione in Individuals with HIV Infection - Devin Morris; Carlos Guerra; Clare Donohue; Hyoung Oh; Melissa Khurasany; Vishwanath Venketaraman (Clinical and Developmental Immunology)
We examined the causes for decreased glutathione (GSH) in individuals with HIV infection. We observed lower levels of intracellular GSH in macrophages from individuals with HIV compared to healthy subjects. Further, the GSH composition found in macrophages from HIV+ subjects heavily favors oxidized glutathione (GSSG) which lacks antioxidant activity, over free GSH which is responsible for GSH’s antioxidant activity. This decrease correlated with an increase in the growth of Mycobacterium tuberculosis (M. tb) in macrophages from HIV+ individuals. In addition, we observed increased levels of free radicals, interleukin-1 (IL-1), interleukin-17 (IL-17) and transforming growth factor-β (TGF-β) in plasma samples derived from HIV+ individuals compared to healthy subjects. We observed decreased expression of the genes coding for enzymes responsible for de novo synthesis of GSH in macrophages derived from HIV+ subjects using quantitative PCR (qPCR). Our results indicate that overproduction of proinflammatory cytokines in HIV+ individuals lead to increased production of free radicals. This combined with the decreased expression of GSH synthesis enzymes leads to a depletion of free GSH and may lead in part to the loss of immune function observed in HIV patients.